A Functional Kinase Is Necessary for Cyclin-Dependent Kinase G1 (CDKG1) to Maintain Fertility at High Ambient Temperature in Arabidopsis - Nibau, Candida; Dadarou, Despoina; Kargios, Nestoras; Mallioura, Areti; Fernandez-Fuentes, Narcis; Cavallari, Nicola; Doonan, John H. (Frontiers in Plant Science, 2020)
Maintaining fertility in a fluctuating environment is key to the reproductive success of flowering plants. Meiosis and pollen formation are particularly sensitive to changes in growing conditions, especially temperature. We have previously identified CDKG1 as a master regulator of temperature-dependent meiosis and this may involve the regulation of alternative splicing, including of its own transcript. CDKG1 mRNA can undergo several alternative splicing events, potentially producing two protein variants: CDKG1L and CDKG1S, differing in their N-terminal domain which may be involved in co-factor interaction. In leaves, both isoforms have distinct temperature-dependent functions on target mRNA processing, but their role in pollen development is unknown. In the present study, we characterise the role of CDKG1L and CDKG1S in maintaining Arabidopsis fertility. We show that the L form is necessary and sufficient to rescue the fertility defects of the cdkg1-1 mutant while the S form is unable to rescue fertility. On the other hand, an extra copy of CDKG1L reduces fertility. In addition, mutation of the ATP binding pocket of the kinase indicates that an active kinase is necessary for the function of CDKG1. Kinase mutants of CDKG1L and CDKG1S correctly localise to the cell nucleus and nucleus and cytoplasm respectively, but are unable to rescue either the fertility or the splicing defects of the cdkg1-1 mutant. Furthermore, we show that there is partial functional overlap between CDKG1 and its paralogue CDKG2 that could in part be explained by overlapping gene expression.